A Study on Students’ Metacognitive Awareness and Their Reading Comprehension - Fatima Zahra; Endang Komariah; Diana Fauzia Sari (Universitas Syiah Kuala, 2016)
This study aimed to find out the correlation between students’ metacognitive awareness and their reading comprehension. The framework of metacognitive awareness is provided by Mokhtari Reichard (2002). A number of 30 students of SMA Laboratorium UNSYIAH Banda Aceh are designated as the sample. In this research the instruments are reading comprehension test and questionnaire. The reading comprehension test and questionnaire were given to the students in order to find the correlation between students’ metacognitive awareness and their reading comprehension. The data was analyzed by using SPSS. The value of correlation of both variables was 0.000 which was less than critical limit of α 0.05 and there was a significant relationship between metacognitive awareness and students’ reading comprehension. There was also a positive correlation between both variables. It means that the more metacognitive awareness the students have the better understanding they have in reading comprehension. In addition, the type of metacognitive awareness strategies which was mostly used by the students was Global Reading Strategies. It is suggested as further studies that another researcher look in depth the cause of Global Reading Strategies applied by the student.